2022
DOI: 10.33650/al-tanzim.v6i4.3461
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of School Management on The Implementation of The Merdeka Belajar Curriculum

Abstract: This research aims to analyze the change of the curriculum into the Merdeka curriculum. The research uses quantitative methods. Data was collected by interviewing the principal and distributing questionnaires to teachers, curriculum development teams, and school management who prepared this curriculum to be developed and collaborated. The implications of this study affect various policies managed by schools and the addition of existing values in institutions, such as the character value of the Pancasila studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Merdeka also puts forward the process of differentiation between students by teachers. In line with that, according to research from (Muhyi et al, 2022), the independent curriculum's characteristics are literacy and numeracy. Research (Ismaya et al, 2021) added that independence is the fulcrum of using relevant technology.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Merdeka also puts forward the process of differentiation between students by teachers. In line with that, according to research from (Muhyi et al, 2022), the independent curriculum's characteristics are literacy and numeracy. Research (Ismaya et al, 2021) added that independence is the fulcrum of using relevant technology.…”
Section: Discussionmentioning
confidence: 66%
“…When conducting observations, trials can be conducted to conduct learning in the observed class. This activity marks the trialability attribute in the 2022 Merdeka curriculum innovation for primary schools (Muhyi et al, 2022).…”
Section: Jip-the Indonesian Journal Of the Social Sciences {521mentioning
confidence: 96%
“…Teachers use methods like flexible grouping, tiered assignments, and learning stations to give students a more tailored education that takes into account their unique interests, aptitudes, and weaknesses. All students will be able to contribute and achieve academic progress with the help of differentiated education (Fathurrahman et al, 2022). Kurikulum Merdeka's implementation features increased emphasis on the use of technology in the classroom.…”
Section: Teaching Strategies In the Impelementation Of Kurikulum Merdekamentioning
confidence: 99%
“…A large number of existing studies in broader literature have examined Merdeka Belajar curriculum as the main subject of the study. Previous studies (Ahid & Sufirmansyah, 2022;Fathurrahman et al, 2022;Prakoso et al, 2021;Setiyaningsih et al, 2022) analyzed the effect of Merdeka Belajar curriculum on the school's management. The school shows readiness to change, revitalize, and add some school policies related to Kurikulum Merdeka Belajar (Fathurrahman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%